Neurodevelopmental outcomes and volumetric analysis of brain in preterm infants with isolated cerebellar hemorrhage - Kim, Seh Hyun; Shin, Seung Han; Yang, Hyo Ju; Park, Seul Gi; Lim, Soo Yeon; Choi, Young Hun; Kim, Ee-Kyung; Kim, Han-Suk (Frontiers in Neurology, 2022)
Background: Cerebellar hemorrhage (CBH) is a major form of cerebellar injury in preterm infants. We aimed to investigate the risk factors and neurodevelopmental outcomes of isolated CBH and performed volumetric analysis at term-equivalent age. Methods: This single-centered nested case-control study included 26 preterm infants with isolated CBH and 52 infants without isolated CBH and any significant supratentorial injury. Results: Isolated CBH was associated with PCO2 fluctuation within 72 h after birth (adjusted odds ratio 1.007, 95% confidence interval 1.000-1.014). The composite score in the motor domain of the Bayley Scales of Infant and Toddler Development at 24 month of corrected age was lower in the punctate isolated CBH group than that in the control group (85.3 vs. 94.5, P = 0.023). Preterm infants with isolated CBH had smaller cerebellum and pons at term-equivalent age compared to the control group. Isolated CBH with adverse neurodevelopment had a smaller ventral diencephalon and midbrain compared to isolated CBH without adverse neurodevelopmental outcomes. Conclusions: In preterm infants, isolated CBH with punctuate lesions were associated with abnormal motor development at 24 months of corrected age. Isolated CBH accompanied by a smaller ventral diencephalon and midbrain at term equivalent had adverse neurodevelopmental outcomes.